Quality-by-design model in optimization of PEG-PLGA nano micelles for targeted cancer therapy - (:unkn) unknown (ELSEVIER SCIENCE BV, 2018)
Poly (D,L-Lactic-co-Glycolic acid) (PLGA) is a biodegradable and biocompatible polymer approved by FDA for clinical uses. Surface functionalization of self-assembly micelles made of PLGA with Poly-Ethylene Glycol (PEG) improves its stability and half-life in blood circulation via inhibiting adsorption of proteins on the surface and consequently decreasing opsonisation rate. The purpose of present study was to optimize PEG amount absorbed on PLGA (PEGabsPLGA) micelles by application of quality by design approach. Based on risk assessment, effect of three variables including PLGA concentration, PEG concentration and molecular weight (MW) of PLGA were studied. Central composite design was implemented for design of experimentation with 26 runs. The PEGabsPLGA nano drug delivery system (NDDS), produced by o/w method, was optimized according to particle size, polydispersity index (PDI) and zeta potential values. Validation of the model was successfully performed with three representative formulations from the design space. As a result, 43.79 mg of PLGA with MW of 30,000-60,000 was incorporated with 12.61 mg of PEG to obtain a 69 nm NDDS (predicted 67.72 nm) with the PDI value equal to 0.124 (predicted 0.112). The results successfully led to the preparation of the most stable nanoparticles which were stable at room temperature for six months.
Keywords: Central composite design; Drug delivery system; PEG-PLGA; Quality by design; Targeted cancer therapy; DRUG-DELIVERY SYSTEMS; IN-VITRO; NANOPARTICLES; NANOSPHERES; SIZE; VIVO